CGIAR submission of its views on the ninth technical expert dialogue (TED) on the New Collective Quantified Goal (NCQG) on Climate Finance - Chilambe, Pedro; Kinyua, Ivy; Ouedraogo, Issa; Jalang'o Anyango, Dorcas; Bowa, Emma; Ravindranath, Darshini; Colombo, Chiara Christina; Salfi, Laura; Stapleton, James; Mukherji, Aditi (CGIAR System Organization, 2024)
CGIAR welcomes the outcomes from COP28 regarding Decision 8/CMA.5 on the New Collective Quantified Goal on Climate Finance and extends its support to the facilitation of science-based evidence to support the definition of the goal, including the structure, timeframe, scope, and sources of funding in respect to food, land, and water systems.